Empowering Muslim Rohingya Youth Refugees: A Baseline Study of Literacy - Suraini Mohd Ali; Hazleena Baharun; Hazlina Abdullah; Dini Farhana Baharudin; Mohd Zaliridzal Zakaria; Habibah Ismail; Noor Saazai Mat Saad; Fariza Puteh Behak (Universiti Sains Islam Malaysia, 2024)
Abqari Vol. 22 (1), 2020